Makna Kode dalam Cerpen Elegi Nyak Betawi Karya K. Usman: Tinjauan Semiotik Barthes: The Meaning of Codes in K. Usman's Short Story Elegi Nyak Betawi: A Barthesian Semiotic Analysis - Jumianti Diana (Transformatika: Jurnal Bahasa, Sastra, dan Pengajarannya, 2026)
This study aims to identify and analyze the five narrative codes and their meanings contained in the short story Elegi Nyak Betawi by K. Usman. The study employed a qualitative research method. Data were collected through a library research method using reading and note-taking techniques. The data were analyzed using a semiotic approach based on Roland Barthes' Five Codes. The results of this study indicate that the short story Elegi Nyak Betawi contains Roland Barthes' five narrative codes, which collectively construct the overall meaning of the text. The hermeneutic code presents enigmas surrounding the identity of the singer, Nyak Betawi's life, and Romdoni's whereabouts, creating narrative tension while conveying themes of loss, longing, and a mother's enduring hope. The semic code represents Nyak Betawi's social identity, character, and emotional condition as an elderly woman living in economic hardship who nevertheless embodies simplicity, resilience, perseverance, diligence, and an unwavering spirit. The symbolic code is manifested through the opposition of meanings expressed in Nyak Betawi's continuous wait for Romdoni and her activity of preparing gado-gado, which symbolize maternal love, hope, struggle, and endurance, while simultaneously highlighting the contrast between hope and loss, as well as affection and filial disobedience. The proairetic code is reflected in the sequence of actions performed by the characters, which not only advances the plot but also reinforces the themes of maternal love, sacrifice, and hope. Meanwhile, the cultural code represents Betawi cultural identity through traditional cuisine, forms of address, social life, family status, occupations, and Islamic religious practices, portraying a society that is simple, religious, communal, and committed to preserving its cultural identity. Overall, these five narrative codes interact to construct the central meanings of the story, emphasizing humanity, maternal love, perseverance, and the preservation of Betawi cultural identity